Compensation payments, procedures and policies towards human-wildlife conflict management: Insights from India. (November 2018) - Karanth, Krithi K.; Gupta, Shriyam; Vanamamalai, Anubhav
Abstract: The effectiveness of compensation payments in mitigating and resolving human-wildlife conflict is globally debated. We examined procedures, types, and payments made for incidents reported in India from 2010 to 2015. Among India's 29 states, 22 (76%) compensated for crop loss, 18 (62%) for property damage, 26 (90%) for livestock depredation, and 28 (97%) for human injury or death. In 2012–2013, a total of 78, 656 conflict incidents were reported from 18 states with complete data. Of these incidents, 73.4% were crop loss and property damage, 20% livestock predation, 6.2% human injury, and 0.4% human death. In 2012–2013, payments totalled $5, 332, 762 (ranging from $0 for no reported incidents in Tripura to $1, 956, 115 for 36, 091 incidents in Karnataka). The average expenditures per incident were $47 for crop and property damage, $74 for livestock, $103 for human injury and $3224 for human death. These numbers underestimate the total extent of conflict because of low reporting rates and unavailability of complete records from all states. We found a lack of policies in some states, while others have low payment amounts along with high transaction costs. Despite a significant Indian government mandate supporting compensation payments in India, there exist inconsistencies in eligibility, application, assessment, implementation, and payment procedures across states. Ensuring that compensation reaches all affected people requires standardizing these processes in a transparent and efficient manner, while also monitoring its perceived benefits to wildlife conservation.